The Influence Of Learning Creative Product And Entrepreneurship Subjects To The Passion Of The Students In Entrepreneurship At Smkn 9 Padang - Andini, Vanisa; Yelfi, Reno (Universitas Negeri Padang, 2023)
this study aims to describe The effect of learning outcomes on creative and entrepreneurial product subjects in the culinary field on the passion of class XII Culinary students in entrepreneurship at SMK N 9 Padang. This research method is a quantitative correlational approach. The results of the study are from the average variable score, creative product learning and entrepreneurship obtain a respondent achievement level (TCR) of 4.14 with a very high category. From the average variable score, the desire for entrepreneurship obtained a respondent achievement level (TCR) of 4.14 in the high category. There is a positive and significant relationship between the learning variables of creative and entrepreneurial products and the desire of Class XII Tata Culinary students to become entrepreneurs at SMKN 9 Padang, where the level of relationship between the two variables is in a fairly strong category.